1999
DOI: 10.1111/j.1469-7793.1999.0485v.x
|View full text |Cite
|
Sign up to set email alerts
|

Temporal overlap of excitatory and inhibitory afferent input in guinea‐pig CA1 pyramidal cells

Abstract: The response to afferent fibre stimulation ('orthodromic response') is a commonly used measure of excitability of neuronal populations. An excitatory (EPSP) and inhibitory (IPSP) component was identified by studies of the orthodromic response in hippocampal pyramidal cells in vivo (Kandel et al. 1961;Andersen et al. 1963Andersen et al. , 1964. This basic sequence of orthodromic EPSP-IPSP has been confirmed since then: the response that is elicited by stimulation of the Schaffer collateral-commissural pathway c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 50 publications
2
50
0
Order By: Relevance
“…By comparing A and C in Figure 7, it appears that shifts in E 50 did not occur in the conditions corresponding to either the floor or saturation states of the inhibitory neurons. We argue that the range of states in which E-S potentiation occurred is precisely the physiological range, because inhibition and excitation are normally recruited in a balanced manner that allows inhibition to have an impact on Ex neuron activity (Galarreta and Hestrin, 1998;Karnup and Stelzer, 1999;Pouille and Scanziani, 2001). Moreover, inhibitory neurons are driven by fewer input fibers than excitatory neurons (Miles, 1990;Marshall et al, 2002), consistent with the data shown in the middle and bottom panels of Figure 6C.…”
Section: E-s Potentiation Occurs In States In Which Inhibition and Exsupporting
confidence: 77%
See 3 more Smart Citations
“…By comparing A and C in Figure 7, it appears that shifts in E 50 did not occur in the conditions corresponding to either the floor or saturation states of the inhibitory neurons. We argue that the range of states in which E-S potentiation occurred is precisely the physiological range, because inhibition and excitation are normally recruited in a balanced manner that allows inhibition to have an impact on Ex neuron activity (Galarreta and Hestrin, 1998;Karnup and Stelzer, 1999;Pouille and Scanziani, 2001). Moreover, inhibitory neurons are driven by fewer input fibers than excitatory neurons (Miles, 1990;Marshall et al, 2002), consistent with the data shown in the middle and bottom panels of Figure 6C.…”
Section: E-s Potentiation Occurs In States In Which Inhibition and Exsupporting
confidence: 77%
“…If all intensities of the Ex neuron I/O curves before and after LTP elicited similar inhibition, then the same EPSP slope led to the same firing probability, and E-S shifts did not occur. Previous results suggest that the physiological state is indeed one in which excitation is balanced with inhibition (Galarreta and Hestrin, 1998;Karnup and Stelzer, 1999;Pouille and Scanziani, 2001). Therefore, our data indicate that a primary mechanism of E-S potentiation is that EPSPs of a fixed slope evoked after LTP have less effective inhibition and thus a greater probability of reaching firing threshold.…”
Section: Mechanisms Underlying E-s Potentiationmentioning
confidence: 63%
See 2 more Smart Citations
“…Tetrodotoxin (TTX), QX-314, gabazine [SR95531 (2-(3-carboxypropyl)-3-amino-6-(4-methoxyphenyl)pyridazinium bromide)], 6-cyano-7-nitroquinoxaline-2,3-dione (CNQX), and (Ϯ)-2-amino-5-phosphopentanoic acid (APV) were purchased from Research Biochemicals (Natick, MA). Biocytin-filled cells were developed as described previously (Karnup and Stelzer, 1999). Briefly, fixed slices were embedded in 10% gelatin and sectioned at 80 m thickness using a vibratome.…”
Section: Introductionmentioning
confidence: 99%